2018
DOI: 10.1186/s13059-018-1591-1
|View full text |Cite
|
Sign up to set email alerts
|

NmeCas9 is an intrinsically high-fidelity genome-editing platform

Abstract: BackgroundThe development of CRISPR genome editing has transformed biomedical research. Most applications reported thus far rely upon the Cas9 protein from Streptococcus pyogenes SF370 (SpyCas9). With many RNA guides, wildtype SpyCas9 can induce significant levels of unintended mutations at near-cognate sites, necessitating substantial efforts toward the development of strategies to minimize off-target activity. Although the genome-editing potential of thousands of other Cas9 orthologs remains largely untapped… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(94 citation statements)
references
References 99 publications
5
89
0
Order By: Relevance
“…3B), and the SpyCas9 target site STS3 in the VEGFA gene ( Fig. 3C; Amrani et al 2018;Edraki et al 2018). In HEK293T cells, AcrIIC3 and AcrIIA4 robustly inhibited genome editing by Nme1/ 2Cas9 and SpyCas9, respectively, as expected ( Fig.…”
Section: Microrna Repression Enables Escape From Anti-crispr Inhibitisupporting
confidence: 74%
“…3B), and the SpyCas9 target site STS3 in the VEGFA gene ( Fig. 3C; Amrani et al 2018;Edraki et al 2018). In HEK293T cells, AcrIIC3 and AcrIIA4 robustly inhibited genome editing by Nme1/ 2Cas9 and SpyCas9, respectively, as expected ( Fig.…”
Section: Microrna Repression Enables Escape From Anti-crispr Inhibitisupporting
confidence: 74%
“…17 The requirement for a unique PAM by the nuclease is potentially useful for certain applications, and it has also been suggested that Cas9 nucleases with requirement for a long PAM might be naturally more specific. 19,20 To test whether we can enhance the activity of this smaller nuclease by the Cas9-CMP fusion strategy, we constructed the SpaCas9HN1HB1, Spa-Cas9HN1H1G, and SpaCas9HN1CHD1 fusion nucleases (Supplementary File S1). We also modified the previously described sgRNA scaffold by introducing a U to A mutation on the crRNA moiety to disrupt a track of five consecutive Us and a corresponding A to U mutation on the tracrRNA moiety to maintain the A-U base pairing (Supplementary File S1).…”
Section: Improvement Of Streptococcus Pasteurianusmentioning
confidence: 99%
“…On the other hand, with >200 Cas9 orthologs predicted from the bacterial genome sequencing data, 15 it is a viable alternative to explore Cas9 diversity to increase targeting density. Indeed, several Cas9 orthologs with distinct PAM requirements have been identified, [16][17][18][19][20][21][22] but the majority of these orthologs appear to be more susceptible than SpyCas9 to target-to-target variation in cellular environments, limiting their widespread adoption.…”
Section: Introductionmentioning
confidence: 99%
“…AcrIIC1 chimeras were created by Golden Gate cloning as follows: the plasmid encoding AcrIIC1 was first linearized at a selected position in the AcrIIC1 coding sequence via around-the-horn PCR; LOV2-, PDZ-and mCherrycoding sequences were then amplified by matching primers introducing optional GS linker encoding sequences and ligated into the linearized vector backbone; point mutations and protein tags were introduced via around-the-horn PCR via the primer overhangs. Annealed oligonucleotides corresponding to the target site sequence were cloned into the hybrid Cas9-sgRNA vectors via SapI (NmeCas9) or BsaI (SauCas9) restriction sites as described previously 20,34 . Supplementary Fig.…”
Section: Construct Design and Cloningmentioning
confidence: 99%